2023
DOI: 10.3390/beverages10010002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Minor Cereals as Non-Traditional Brewing Raw Materials

Francesca Nocente,
Elena Galassi,
Federica Taddei
et al.

Abstract: Recently, “minor” cereals have been gaining interest due to their distinctive characteristics, not only in terms of nutritional and health potential, but also because of their hardiness. To date, the use of several of these cereals for the production, both at artisan and industrial level, of foods such as pasta and bakery products has already been well established, whereas their investigation for the production of malt and beer has been more limited. In this work, a preliminary analysis of the malting aptitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…F. Nocente et al (2023) showed that fermented beverages made from single-grain, tritordeum, edible sorghum, and teff may be of interest for light and gluten-free beer markets. L. Van Donkelaar et al (2019) found beer produced with added enzymes reduced the use of water, raw materials, and natural gas by 7, 14, and 78%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…F. Nocente et al (2023) showed that fermented beverages made from single-grain, tritordeum, edible sorghum, and teff may be of interest for light and gluten-free beer markets. L. Van Donkelaar et al (2019) found beer produced with added enzymes reduced the use of water, raw materials, and natural gas by 7, 14, and 78%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…F. Nocente et al (2023) showed that fermented beverages made from single-grain, tritordeum, edible sorghum, and teff may be of interest for light and gluten-free beer markets. L. Van Donkelaar et al (2019) found beer produced with added enzymes reduced the use of water, raw materials, and natural gas by 7, 14, and 78%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%